STUDI PERBANDINGAN VUE COMPONENT LIBRARY/FRAMEWORK: VUETIFY, BUEFY, BOOTSTRAPVUE MENGGUNAKAN GTMETRIX - andi semma (Universitas Palangka Raya, 2022)
Developing a web application from scratch is relatively hard as it requires writing a large amount of code. Maintaining the code when it comes to evolve becomes quite tedious. Therefore, using a framework will simplify the process. Using a CSS framework will lift developers’s web designing process as it does the hard work for developers, especially Component framework as it provides a large range of components and attributes. However, when building a simple web application, developers usually do not need a full-fledged framework as it will come with a downside on performance and bundle size. In this article we will discuss three popular vue component libraries/frameworks and test its performance using GTmetrix so this can become a variable of consideration when choosing components framework.